A comprehensive dataset for home appliance control using ERP-based BCIs with the application of inter-subject transfer learning - Lee, Jongmin; Kim, Minju; Heo, Dojin; Kim, Jongsu; Kim, Min-Ki; Lee, Taejun; Park, Jongwoo; Kim, HyunYoung; Hwang, Minho; Kim, Laehyun; Kim, Sung-Phil (Frontiers in Human Neuroscience, 2024)
Brain-computer interfaces (BCIs) have a potential to revolutionize human-computer interaction by enabling direct links between the brain and computer systems. Recent studies are increasingly focusing on practical applications of BCIse.g., home appliance control just by thoughts. One of the non-invasive BCIs using electroencephalography (EEG) capitalizes on event-related potentials (ERPs) in response to target stimuli and have shown promise in controlling home appliance. In this paper, we present a comprehensive dataset of online ERP-based BCIs for controlling various home appliances in diverse stimulus presentation environments. We collected online BCI data from a total of 84 subjects among whom 60 subjects controlled three types of appliances (TV: 30, door lock: 15, and electric light: 15) with 4 functions per appliance, 14 subjects controlled a Bluetooth speaker with 6 functions via an LCD monitor, and 10 subjects controlled air conditioner with 4 functions via augmented reality (AR). Using the dataset, we aimed to address the issue of inter-subject variability in ERPs by employing the transfer learning in two different approaches. The first approach, 'withinparadigm transfer learning,' aimed to generalize the model within the same paradigm of stimulus presentation. The second approach, 'cross-paradigm transfer learning,' involved extending the model from a 4-class LCD environment to different paradigms. The results demonstrated that transfer learning can effectively enhance the generalizability of BCIs based on ERP across different subjects and environments.